Moral disengagement and fear of retaliation: why adolescents choose to be passive bystanders to school bullying - ChangJun Goh; Tomas Jungert (Social Psychology of Education, 2026)
Abstract This study examined the potential functional overlap between fear of retaliation and moral disengagement as justifications for peer bystander inaction in school bullying. Although often treated as distinct barriers to intervention, the study investigated whether fear of retaliation could function as a self-exonerating justification to reconcile inconsistencies between one’s moral standards and passive behavior, similar to moral disengagement, and whether the two constructs empirically overlap. 163 students (aged 15–16) justified their decisions about defending victims in hypothetical school bullying scenarios. Justifications included fear of retaliation, moral disengagement, downplaying of risk, and moral engagement. Results from linear mixed-effects models showed convergence between fear- and disengagement-based justifications across phases, with endorsements of disengagement increasing under conditions involving cues suggestive of social support. Gender-stratified analyses further indicated that this convergence occurred more consistently among female participants. The findings refine theoretical models of bystander behavior and suggest that fear-based justifications can sometimes serve self-exculpatory functions in situations involving cognitive dissonance. Therefore, interventions may benefit from addressing both fear- and disengagement-based justifications for inaction to promote peer intervention in schools.